Graduate Employment in Vietnam - Tong, Linh (International Higher Education, 2019)
As of 2018, it is mandatory for Vietnamese higher education institutions (HEIs) to publish the employment rates of their graduates. Failure to comply with this regulation will automatically disqualify accredited HEIs from the right to recruit new students. So far, less than 5 percent of Vietnamese HEIs have published employment rates for their alumni and there is a lot of criticism and suspicion from the public toward the reliability of these statistics. The ministry of education and training should either conduct a national employability survey or establish an accreditation agency to monitor the surveying process, rather than leaving this task to voluntary cooperation from universities.